ANALISIS KINERJA RANTAI PASOK DAN NILAI TAMBAH PRODUK OLAHAN KELOMPOK WANITA TANI MELATI DI DESA TRIBUDISYUKUR KECAMATAN KEBUN TEBU LAMPUNG BARAT - Sartika Lestari; Zainal Abidin; Suarno Sadar (Lampung University, 2016)
This study purposed to measure supply chain performance of KWT Melati products and analyze value added of KWT Melati products. This Research was conducted in Tribudisyukur Village at Kebun Tebu Subdistrict, West Lampung. The research data was collected on April 2015 using survey method. Sample size was 25 respondents who were selected using purposive sampling. Analysis Data Method used for supply chain management performance was Supply Chain Operation References (SCOR) 9,0 and for value added analysis was Hayami method. The result of this study showed that (1) Based on the result of this study, there is an ineffectiveness on management cost especially on Total Supply Chain Management Cost (TSMC) metric for all products of KWT Melati, this is caused by the amount of cost spent on producing (2) The most profitable product of KWT Melati is coffee package 25gr with value added ratio 55,68% and gave added value Rp52.400,00 for every kg coffee production. Key words : women farmer group, supply chain performance, value added analysis